Agreement and interpretation of binominals in French - An, Aixiu; Abeillé, Anne (Proceedings of the 24th International Conference on Head-Driven Phrase Structure Grammar, 2017)
This paper investigates the structure and agreement of coordinated binominals in the form Det N1 et N2 in French. We provide corpus data and experimental data to show that different strategies exist, depending on their readings: singular Det for joint reading (mon collègue et ami, 'my.MSG colleague.MSG and friend.MSG'), plural Det agreement (mes frère et soeur 'my.PL brother.MSG and sister.FSG') or closest conjunct agreement (mon nom et prénom, 'my.MSG surname.MSG and first name.MSG') for split reading. These results challenge previous syntactic analyses of binominals (Le Bruyn and de Swart, 2014), stating that Det combines with N1, forming a DP and the later coordinates with N2. We then propose an HPSG analysis to account for French binominals.